Preparation method of high-strength high-white high-transparency type jade porcelain

CN123003272APending Publication Date: 2026-10-30JINGDEZHEN CERAMIC UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202611496991.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

例如,CN109081678A实现抗折强度90~105MPa、白度75~78%;CN109608181A将抗折强度提升至125MPa以上,但未涉及白度优化;CN105060843A、CN105218070A分别将白度提升至92~94%和85.6~87.2%,却未提供强度数据;CN113800880A断裂模数为52~57MPa,但未优化白度与透光性;CN119977522A实现透光度>55%并降低高温形变;CN114436626B亦侧重高透低变形,但二者均未涉及白度与抗折强度的优化

Benefits of technology

本发明通过构建“双高岭土基体设计—分步球磨活化—精准控铁高钠助熔—改性增韧”协同体系,在原料成本更具优势的条件下,实现了高白度、高透光性与高强度高韧性的统一,具有以下突出的有益效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003272A_ABST
    Figure CN123003272A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of high-strength high-whiteness high-transparency jade-type porcelain, which comprises basic raw material A and other added raw material B, and the weight percentage composition of the basic raw material A is as follows: 40-52% of potassium feldspar, 12-28% of Guangxi kaolin, 18-28% of quartz, 6-20% of Malaysia kaolin and 1-5% of bentonite; the other added raw material B is added according to the total weight of the basic raw material A, and the other added raw material B is composed of 0.5-10% of alumina, 2-3% of eucryptite, 5-13% of Malaysia kaolin and 0-4% of zirconia; the basic raw material A and the other added raw material B are respectively subjected to wet ball milling to obtain slurries; the slurries are subjected to dehydration, drying, crushing and sieving to obtain molding raw materials; the molding raw materials of the other added raw material B are pre-fired, crushed, sieved and then mixed with the molding raw materials of the basic raw material A to obtain mixed billets through ball milling; and the high-strength high-whiteness high-transparency jade-type porcelain is obtained through granulation, molding, drying of green bodies, and firing in a reducing atmosphere.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of inorganic non-metallic materials, and particularly relates to a method for preparing high-strength, high-whiteness, and high-transparency jade-like porcelain. Background Technology

[0002] Jade-like porcelain, as a high-end branch of feldspar porcelain, occupies an important position in the field of high-end daily-use and art ceramics due to its warm and delicate texture and good translucency. Its strength, whiteness, and translucency are core indicators for measuring product quality. In existing technologies, some solutions have already explored optimization around these two indicators. For example, CN109081678A achieves a flexural strength of 90–105 MPa and a whiteness of 75–78%; CN109608181A increases the flexural strength to over 125 MPa, but does not involve whiteness optimization; CN105060843A and CN105218070A increase the whiteness to 92–94% and 85.6–87.2% respectively, but do not provide strength data; CN113800880A has a modulus of rupture of 52–57 MPa, but does not optimize whiteness and light transmittance; CN119977522A achieves light transmittance >55% and reduces high-temperature deformation; CN114436626B also focuses on high transmittance and low deformation, but neither of them involves whiteness and flexural strength optimization. CN105060843A achieves high whiteness through a low-iron kaolin-feldspar-quartz system, but this technology still follows the traditional "low-iron whitening" approach, relying on ultra-pure raw materials and failing to resolve the inherent contradiction between strength, whiteness, and translucency. It is evident that existing technologies often focus on a single performance characteristic, making it difficult to achieve a synergistic improvement across all three. The reason for this lies in the inherent contradiction between whiteness, strength, and translucency in feldspar porcelain: improving whiteness requires strict control of iron and titanium content (Fe2O3 < 0.25%), but raw materials are limited and sintering activity decreases; improving strength depends on the development of mullite crystal phases, but this increases light scattering and reduces translucency; improving translucency requires reducing porosity and grain boundaries, but excessive densification weakens mechanical properties. This constraint makes it difficult to simultaneously improve all three indicators, constituting a technological bottleneck.

[0003] To address these contradictions, existing approaches each have their limitations: selecting high-purity raw materials is costly and lacks sufficient strength; introducing toughening phases easily leads to agglomeration, which in turn impairs whiteness and light transmittance; adding low-temperature fluxes improves densification but reduces high-temperature strength. None of these three approaches solves the problem of synergistic improvement at the material design level. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing high-strength, high-whiteness, and high-transparency jade-like porcelain that is low in cost, simple in process, and has excellent performance.

[0005] This invention is achieved through the following technical solution: A method for preparing a high-strength, high-whiteness, and high-transparency jade-like porcelain, characterized by comprising: a basic raw material A and other additive raw materials B. The weight percentage composition of the basic raw material A is as follows: potassium feldspar 40-52%, Guangxi kaolin 12-28%, quartz 18-28%, Malaysian kaolin 6-20%, and bentonite 1-5%; The other additive raw material B is added according to the total weight of the base raw material A, namely 0.5-10% alumina, 2-3% litharge, 5-13% Malaysian kaolin, and 0-4% nano-zirconia; The preparation method comprises the following steps: Step 1: Wet ball mill the base raw material A and other additive raw material B separately, and then pass them through an 80-120 mesh sieve to obtain the base raw material A slurry and the other additive raw material B slurry; Step 2: Pour the base material A slurry and the other additive material B slurry obtained in Step 1 into a plaster mold for dehydration and molding. Place the base material A blank and the other additive material B blank obtained after demolding in an oven to dry. Step 3: Crush the dried base material A blank and other additive material B blank into powder respectively, add water to adjust the moisture content of the powder to 5-7%, and then pass them through a 40-mesh sieve to obtain the base material A molding material and other additive material B molding material respectively. Step 4: Pre-fire the other added raw material B molding material at 750-850℃ for 200-300 minutes. After crushing, pass it through a 120-150 mesh sieve. Then mix it with the base raw material A molding material and dry ball mill for 3-5 minutes to obtain a uniformly mixed jade porcelain mixed blank. Step 5: The jade-like porcelain mixed raw material obtained in Step 4 is granulated, shaped, dried, and fired in a reducing atmosphere to obtain high-strength, high-whiteness, and high-transparency jade-like porcelain.

[0006] In step one, the material-to-milling ball-to-water mass ratio in the wet ball milling process is 1:1.8-2:0.5-1, the ball milling speed is 350 r / min, and the ball milling time is 10-25 min.

[0007] The drying process in step two is carried out at a temperature of 70–100°C for 10–16 hours.

[0008] The particle size of the powder in the granulation process in step five is sieve size of 40 mesh.

[0009] In step five, the molding pressure is 10–20 MPa and the holding time is 8–10 s.

[0010] In step five, the temperature for drying the green body is 70–100°C, and the time is 10–18 hours.

[0011] The firing process in step five involves uniformly raising the temperature from room temperature to 1260-1320°C over 10-16 hours, holding it at that temperature for 30-60 minutes, and then allowing it to cool naturally back to room temperature.

[0012] The high-strength, high-whiteness, and high-transparency jade-like porcelain obtained in step five has a flexural strength of 104.83–128.76 MPa, a whiteness of 94.63–95.35%, and a light transmittance of 26.5–28.8%.

[0013] The present invention has the following beneficial effects: This invention, by constructing a synergistic system of "dual kaolin matrix design—stepwise ball milling activation—precise control of iron and high sodium fluxing—modification and toughening," achieves a balance between high whiteness, high light transmittance, high strength, and high toughness while maintaining a more advantageous raw material cost. It possesses the following outstanding beneficial effects: (1) This invention breaks through the technical prejudice that traditional high-white porcelain must strictly control the iron content. It utilizes a high-sodium glass phase to transform a specific iron content (0.35wt%) from a harmful coloring impurity into a highly efficient mineralizer. This mineralizer significantly promotes the melting of quartz and the development of mullite microcrystals, reduces the sintering temperature, and broadens the firing range. At the same time, it effectively inhibits iron ion coloring through the encapsulation and stabilization effect of the low-viscosity glass phase, achieving high whiteness under the condition of more advantageous raw material cost.

[0014] (2) Traditional jade porcelain requires strict control of iron content below 0.25% to ensure whiteness. However, this invention breaks through this technical bias and uses Malaysian kaolin to reveal for the first time the in-situ synergistic mechanism of high sodium (5.1wt%) and high iron (0.35wt%): The high sodium-formed high-activity, low-viscosity melt, on the one hand, enables iron ions to preferentially form ferrite polyhedra and induce them to enter the mullite lattice, transforming iron from a free coloring state to a lattice-locked state and eliminating its coloring ability; on the other hand, the activated iron ions act as an interfacial surfactant to reduce the liquid-solid interfacial tension, promote the melt to wet quartz particles, and act as an electron transfer bridge to accelerate the breaking and recombination of Si-O and Al-O bonds, significantly reducing the activation energy of mullite crystallization and promoting a large number of nucleations and developments at low temperatures; at the same time, the melt uniformly encapsulates iron ions inside the glass network and provides an ideal carrier for the toughening phase to be extremely uniformly dispersed. The synergistic effect of the three mechanisms enables the invention to simultaneously improve high whiteness, high strength and high light transmittance without relying on ultrapure raw materials. This breaks through the technical prejudice that traditional jade porcelain must strictly control iron content and provides a brand-new material design path for the preparation of high-performance jade porcelain.

[0015] (3) This invention introduces a pre-firing activation process into the jade-like porcelain body formulation, pre-firing other additive raw materials B (containing Malaysian kaolin, alumina, nano-zirconia, and lithium feldspar) at 750-850℃. This causes the Malaysian kaolin to form a metastable residual phase: long-range disordered but short-range ordered, enriched with unsaturated bonds and oxygen vacancies, and possessing high chemical reactivity. During subsequent firing, this metastable residual phase undergoes chemical transformation with high-sodium melt, alumina, and active SiO2, inducing uniform fine-grained mullite to precipitate in situ inside the body. This low-temperature crystallization pathway is deeply coupled with the synergistic effect of high sodium (5.1wt%) and high iron (0.35wt%) in the formulation—the high-sodium melt further lowers the mullite crystallization energy barrier, creating a favorable chemical environment, allowing the fine-grained mullite interwoven network and residual quartz particles to form a composite reinforcing skeleton, significantly improving the material's mechanical properties (flexural strength 104.83-128.76 MPa).

[0016] (4) This invention utilizes a high-quality, low-viscosity, and highly wettable glassy phase formed by the synergistic interaction of iron and sodium as a dispersion carrier for toughening phase particles (nano-zirconia, alumina, etc.), effectively solving the technical problem of easy agglomeration of toughening phase in ceramic matrix. The uniformly dispersed toughening phase particles form a good interfacial bond with the matrix, enabling the phase transformation energy to be absorbed with maximum efficiency when cracks propagate to the toughening phase particles, thus significantly improving the toughness of the material.

[0017] (5) In this invention, the other additive raw material B is pre-calcined and pulverized before being mixed with the base raw material A and dry-milled. This ensures that the two raw materials reach their respective optimal particle size distribution, avoiding the particle size unevenness caused by the difference in milling rate between raw materials of different hardness (hard quartz, feldspar, and soft kaolin) in a single ball milling process. At the same time, the pre-calcined components in the other additive raw material B are more easily and evenly dispersed in the base raw material A during dry ball milling. This process ensures the uniform distribution of each functional component in the green body and maximizes its reactivity.

[0018] (6) The present invention employs a reducing atmosphere firing process, which works synergistically with the high iron content in the formula: the reducing atmosphere facilitates the reduction of Fe2O3 to FeO and its entry into the glass network, significantly improving the whiteness of the green body; at the same time, the reducing atmosphere can reduce the viscosity of the liquid phase, promote the uniform spreading of the glass phase, reduce scattering centers, and improve light transmittance. This firing process and the formula composition together constitute a key technology combination for achieving high transmittance and high whiteness.

[0019] (7) By functionalizing kaolin with higher Fe2O3 (0.35wt%), this invention breaks through the traditional technical prejudice that the iron content must be lower than 0.25wt%, and reveals the in-situ synergistic effect of high sodium and high iron in the formulation, so that iron is transformed from a harmful coloring impurity into an efficient mineralizer.

[0020] This invention achieves simultaneous improvement in high whiteness, high strength, and high light transmittance without relying on ultrapure raw materials, and provides a brand-new ceramic material design methodology—breaking through performance bottlenecks by precisely controlling "impurities" and creatively combining elements, which is of great value in promoting the green and low-cost development of the ceramic materials field. Attached Figure Description

[0021] Figure 1 The images show actual photographs of different jade porcelain samples under light in a dark environment, including: (A) the jade porcelain sample obtained in Example 2, (B) the high-transparency jade porcelain sample currently on the market, (C) the jade porcelain sample obtained in Comparative Example 1, and (D) the jade porcelain sample obtained in Comparative Example 2. Figure 2 This is an SEM image of the jade porcelain sample obtained in Example 2 of the present invention; Figure 3 The image shows the XRD pattern of the jade-like porcelain sample obtained in Example 2 of this invention. Detailed Implementation

[0022] To further illustrate the present invention, the technical means and effects adopted to achieve the intended purpose of the invention, the present invention will be described in detail below with reference to preferred embodiments: The raw materials used in the embodiments of this invention—potassium feldspar, Guangxi kaolin, quartz, Malaysian kaolin, lithium feldspar, bentonite, alumina, and nano-zirconia—are all industrial-grade raw materials and can be purchased commercially. The specific chemical composition (wt%) of each raw material is shown in Table 1 below, obtained by X-ray fluorescence spectroscopy (XRF) analysis. In the table, "-" indicates that the corresponding component has extremely low content or is absent and can be ignored.

[0023] .

[0024] Example 1 A method for preparing a high-strength, high-whiteness, and high-transparency jade-like porcelain, characterized by comprising: a basic raw material A and other additive raw materials B. The weight percentage composition of the basic raw material A is as follows: potassium feldspar 49%, Guangxi kaolin 20%, quartz 18%, Malaysian kaolin 10%, and bentonite 3%; The other additive material B is added according to the total weight of the base material A, consisting of 10% alumina, 2% lithium feldspar, 5% Malaysian kaolin, and 0% nano-zirconia. The preparation method comprises the following steps: Step 1: Wet ball mill the base raw material A and other additive raw material B separately, and then pass them through a 120-mesh sieve to obtain the base raw material A slurry and the other additive raw material B slurry; Step 2: Pour the base material A slurry and the other additive material B slurry obtained in Step 1 into a plaster mold for dehydration and molding. Place the base material A blank and the other additive material B blank obtained after demolding in an oven to dry. Step 3: Crush the dried base material A blank and other additive material B blank into powder, add water to adjust the powder moisture content to 5%, and then pass them through a 40-mesh sieve to obtain base material A molding material and other additive material B molding material respectively. Step 4: First, pre-fire the other added raw material B molding material at 850℃ for 200 minutes, then crush it and pass it through a 150-mesh sieve. Then mix it with the base raw material A molding material and dry ball mill for 3 minutes to obtain a uniformly mixed jade porcelain mixed blank. Step 5: The jade-like porcelain mixed raw material obtained in Step 4 is granulated, shaped, dried, and fired in a reducing atmosphere to obtain high-strength, high-whiteness, and high-transparency jade-like porcelain.

[0025] In step one, the wet ball milling process has a material-to-milling ball-to-water mass ratio of 1:2:1, a milling speed of 350 r / min, and a milling time of 25 min.

[0026] The drying process in step two is carried out at a temperature of 100°C for 12 hours.

[0027] The particle size of the powder in the granulation process in step five is sieve size of 40 mesh.

[0028] In step five, the molding pressure is 12 MPa and the holding time is 10 seconds.

[0029] In step five, the green body is dried at a temperature of 100°C for 18 hours.

[0030] The firing process in step five involves uniformly raising the temperature from room temperature to 1280°C over 16 hours, holding it at that temperature for 60 minutes, and then allowing it to cool naturally back to room temperature.

[0031] The high-strength, high-whiteness, and high-transparency jade-like porcelain obtained in step five has a flexural strength of 109.48 MPa, a whiteness of 94.63%, and a light transmittance of 27.9%.

[0032] Example 2 A method for preparing a high-strength, high-whiteness, and high-transparency jade-like porcelain, characterized by comprising: a basic raw material A and other additive raw materials B. The weight percentage composition of the basic raw material A is as follows: potassium feldspar 40%, Guangxi kaolin 20%, quartz 18%, Malaysian kaolin 20%, and bentonite 2%. The other additive raw material B is added according to the total weight of the base raw material A, namely 0.5% alumina, 2% lithium feldspar, 5% Malaysian kaolin, and 4% nano-zirconia; The preparation method comprises the following steps: Step 1: Wet ball mill the base raw material A and other additive raw material B separately, and then pass them through a 100-mesh sieve to obtain the base raw material A slurry and the other additive raw material B slurry; Step 2: Pour the base material A slurry and the other additive material B slurry obtained in Step 1 into a plaster mold for dehydration and molding. Place the base material A blank and the other additive material B blank obtained after demolding in an oven to dry. Step 3: Crush the dried base material A blank and other additive material B blank into powder respectively, add water to adjust the powder moisture content to 6.5%, and then pass them through a 40-mesh sieve to obtain the base material A molding material and other additive material B molding material respectively; Step 4: First, pre-fire the other added raw material B molding material at 750℃ for 300 minutes, then crush it and pass it through a 120-mesh sieve. Then mix it with the base raw material A molding material and dry ball mill for 3 minutes to obtain a uniformly mixed jade porcelain mixed blank. Step 5: The jade-like porcelain mixed raw material obtained in Step 4 is granulated, shaped, dried, and fired in a reducing atmosphere to obtain high-strength, high-whiteness, and high-transparency jade-like porcelain.

[0033] In step one, the wet ball milling process has a material:milling ball:water mass ratio of 1:2:0.5, a ball milling speed of 350 r / min, and a ball milling time of 15 min.

[0034] The drying process in step two is carried out at a temperature of 100°C for 10 hours.

[0035] The particle size of the powder in the granulation process in step five is sieve size of 40 mesh.

[0036] In step five, the molding pressure is 20 MPa and the holding time is 8 seconds.

[0037] In step five, the green body is dried at a temperature of 100°C for 12 hours.

[0038] The firing process in step five involves uniformly raising the temperature from room temperature to 1320°C over 16 hours, holding it at that temperature for 30 minutes, and then allowing it to cool naturally back to room temperature.

[0039] The high-strength, high-whiteness, and high-transparency jade-like porcelain obtained in step five has a flexural strength of 128.76 MPa, a whiteness of 95.35%, and a light transmittance of 28.8%.

[0040] Depend on Figure 1 It is evident that the jade porcelain sample (A) of this invention is superior to the currently available high-transparency jade porcelain samples (B), comparative example (C), and comparative example (D) in terms of aperture and transparency.

[0041] SEM phase analysis was performed on the sample of this invention, and the results are shown in the figure. Figure 2 and Figure 3 .

[0042] from Figure 2 As can be seen, the sample consists of a large amount of glass phase, and a few crystals are distributed on its surface.

[0043] from Figure 3 As can be seen from the data, the main crystalline phases of the sample are mullite, quartz, alumina and zirconium oxide; the formation of a large amount of glass phase in the system is the key to its improved light transmittance, while the precipitation of mullite crystal phase, combined with the synergistic strengthening effect of alumina and nano-zirconia, gives the sample its high mechanical strength.

[0044] Example 3 A method for preparing a high-strength, high-whiteness, and high-transparency jade-like porcelain, characterized by comprising: a basic raw material A and other additive raw materials B. The weight percentage composition of the basic raw material A is as follows: potassium feldspar 52%, Guangxi kaolin 12%, quartz 26%, Malaysian kaolin 9%, and bentonite 1%; The other additive material B is added according to the total weight of the base material A, namely 10% alumina, 3% lepidolite, 13% Malaysian kaolin, and 1% nano-zirconia. The preparation method comprises the following steps: Step 1: Wet ball mill the base raw material A and other additive raw material B separately, and then pass them through an 80-mesh sieve to obtain the base raw material A slurry and the other additive raw material B slurry; Step 2: Pour the base material A slurry and the other additive material B slurry obtained in Step 1 into a plaster mold for dehydration and molding. Place the base material A blank and the other additive material B blank obtained after demolding in an oven to dry. Step 3: Crush the dried base material A blank and other additive material B blank into powder respectively, add water to adjust the moisture content of the powder to 7%, and then pass them through a 40-mesh sieve to obtain the base material A molding material and other additive material B molding material respectively. Step 4: First, pre-fire the other additive raw material B at 750℃ for 300 minutes, then crush it and pass it through a 120-mesh sieve. Then, mix it with the base raw material A and dry ball mill it for 5 minutes to obtain a uniformly mixed jade porcelain blank. Step 5: The jade-like porcelain mixed raw material obtained in Step 4 is granulated, shaped, dried, and fired in a reducing atmosphere to obtain high-strength, high-whiteness, and high-transparency jade-like porcelain.

[0045] In step one, the wet ball milling process has a material-to-milling ball-to-water mass ratio of 1:2:1, a milling speed of 350 r / min, and a milling time of 20 min.

[0046] The drying process in step two is carried out at a temperature of 70°C for 12 hours.

[0047] The particle size of the powder in the granulation process in step five is sieve size of 40 mesh.

[0048] In step five, the molding pressure is 15 MPa and the holding time is 10 seconds.

[0049] In step five, the green body is dried at a temperature of 70°C for 12 hours.

[0050] The firing process in step five involves uniformly raising the temperature from room temperature to 1300°C over 10 hours, holding it at that temperature for 60 minutes, and then allowing it to cool naturally back to room temperature.

[0051] The high-strength, high-whiteness, and high-transparency jade-like porcelain obtained in step five has a flexural strength of 107.59 MPa, a whiteness of 94.70%, and a light transmittance of 28.1%.

[0052] Example 4 A method for preparing a high-strength, high-whiteness, and high-transparency jade-like porcelain, characterized by comprising: a basic raw material A and other additive raw materials B. The weight percentage composition of the basic raw material A is as follows: potassium feldspar 40%, Guangxi kaolin 20%, quartz 28%, Malaysian kaolin 9%, and bentonite 3%; The other additive material B is added according to the total weight of the base material A, namely 8% alumina, 2.5% litharge, 13% Malaysian kaolin, and 3% nano-zirconia; The preparation method comprises the following steps: Step 1: Wet ball mill the base raw material A and other additive raw material B separately, and then pass them through a 100-mesh sieve to obtain the base raw material A slurry and the other additive raw material B slurry; Step 2: Pour the base material A slurry and the other additive material B slurry obtained in Step 1 into a plaster mold for dehydration and molding. Place the base material A blank and the other additive material B blank obtained after demolding in an oven to dry. Step 3: Crush the dried base material A blank and other additive material B blank into powder respectively, add water to adjust the moisture content of the powder to 7%, and then pass them through a 40-mesh sieve to obtain the base material A molding material and other additive material B molding material respectively. Step 4: First, pre-fire the other additive raw material B at 800℃ for 250 minutes, then crush it and pass it through a 120-mesh sieve. Then, mix it with the base raw material A and dry ball mill it for 4 minutes to obtain a uniformly mixed jade porcelain mixed blank. Step 5: The jade-like porcelain mixed raw material obtained in Step 4 is granulated, shaped, dried, and fired in a reducing atmosphere to obtain high-strength, high-whiteness, and high-transparency jade-like porcelain.

[0053] In step one, the wet ball milling process has a material-to-milling ball-to-water mass ratio of 1:2:1, a milling speed of 350 r / min, and a milling time of 15 min.

[0054] The drying process in step two is carried out at a temperature of 80°C for 16 hours.

[0055] The particle size of the powder in the granulation process in step five is sieve size of 40 mesh.

[0056] In step five, the molding pressure is 12 MPa and the holding time is 8 seconds.

[0057] In step five, the green body is dried at a temperature of 100°C for 10 hours.

[0058] The firing process in step five involves uniformly raising the temperature from room temperature to 1320°C over 10 hours, holding it at that temperature for 40 minutes, and then allowing it to cool naturally back to room temperature.

[0059] The high-strength, high-whiteness, and high-transparency jade-like porcelain obtained in step five has a flexural strength of 104.83 MPa, a whiteness of 95.15%, and a light transmittance of 27.5%.

[0060] Example 5 A method for preparing a high-strength, high-whiteness, and high-transparency jade-like porcelain, characterized by comprising: a basic raw material A and other additive raw materials B. The weight percentage composition of the basic raw material A is as follows: potassium feldspar 40%, Guangxi kaolin 28%, quartz 18%, Malaysian kaolin 9%, bentonite 5%; The other additive material B is added according to the total weight of the base material A, namely 10% alumina, 3% lepidolite, 13% Malaysian kaolin, and 3% nano-zirconia. The preparation method comprises the following steps: Step 1: Wet ball mill the base raw material A and other additive raw material B separately, and then pass them through an 80-mesh sieve to obtain the base raw material A slurry and the other additive raw material B slurry; Step 2: Pour the base material A slurry and the other additive material B slurry obtained in Step 1 into a plaster mold for dehydration and molding. Place the base material A blank and the other additive material B blank obtained after demolding in an oven to dry. Step 3: Crush the dried base material A blank and other additive material B blank into powder respectively, add water to adjust the moisture content of the powder to 7%, and then pass them through a 40-mesh sieve to obtain the base material A molding material and other additive material B molding material respectively. Step 4: First, pre-fire the other additive raw material B at 750℃ for 300 minutes, then crush it and pass it through a 130-mesh sieve. Then, mix it with the base raw material A and dry ball mill it for 3 minutes to obtain a uniformly mixed jade porcelain mixed blank. Step 5: The jade-like porcelain mixed raw material obtained in Step 4 is granulated, shaped, dried, and fired in a reducing atmosphere to obtain high-strength, high-whiteness, and high-transparency jade-like porcelain.

[0061] In step one, the wet ball milling process has a material-to-ball-to-water mass ratio of 1:1.8:0.75, a ball milling speed of 350 r / min, and a ball milling time of 20 min.

[0062] The drying process in step two is carried out at a temperature of 100°C for 12 hours.

[0063] The particle size of the powder in the granulation process in step five is sieve size of 40 mesh.

[0064] In step five, the molding pressure is 20 MPa and the holding time is 9 seconds.

[0065] In step five, the green body is dried at a temperature of 80°C for 16 hours.

[0066] The firing process in step five involves uniformly raising the temperature from room temperature to 1260°C over 16 hours, holding it at that temperature for 60 minutes, and then allowing it to cool naturally back to room temperature.

[0067] The high-strength, high-whiteness, and high-transparency jade-like porcelain obtained in step five has a flexural strength of 113.12 MPa, a whiteness of 95.20%, and a light transmittance of 26.5%.

[0068] Example 6 A method for preparing a high-strength, high-whiteness, and high-transparency jade-like porcelain, characterized by comprising: a basic raw material A and other additive raw materials B. The weight percentage composition of the basic raw material A is as follows: potassium feldspar 50%, Guangxi kaolin 20%, quartz 18%, Malaysian kaolin 9%, bentonite 3%; The other additive material B is added according to the total weight of the base material A, namely 10% alumina, 3% lepidolite, 13% Malaysian kaolin, and 2% nano-zirconia. The preparation method comprises the following steps: Step 1: Wet ball mill the base raw material A and other additive raw material B separately, and then pass them through an 80-mesh sieve to obtain the base raw material A slurry and the other additive raw material B slurry; Step 2: Pour the base material A slurry and the other additive material B slurry obtained in Step 1 into a plaster mold for dehydration and molding. Place the base material A blank and the other additive material B blank obtained after demolding in an oven to dry. Step 3: Crush the dried base material A blank and other additive material B blank into powder respectively, then add water to adjust the powder moisture content to 6.8%, and then pass them through a 40-mesh sieve to obtain the base material A molding material and other additive material B molding material respectively; Step 4: First, pre-fire the other added raw material B molding material at 750℃ for 300 minutes, then crush it and pass it through a 140-mesh sieve. Then mix it with the base raw material A molding material and dry ball mill for 4 minutes to obtain a uniformly mixed jade porcelain mixed blank. Step 5: The jade-like porcelain mixed raw material obtained in Step 4 is granulated, shaped, dried, and fired in a reducing atmosphere to obtain high-strength, high-whiteness, and high-transparency jade-like porcelain.

[0069] In step one, the wet ball milling process has a material-to-milling ball-to-water mass ratio of 1:2:1, a milling speed of 350 r / min, and a milling time of 15 min.

[0070] The drying process in step two is carried out at a temperature of 100°C for 12 hours.

[0071] The particle size of the powder in the granulation process in step five is sieve size of 40 mesh.

[0072] In step five, the molding pressure is 10 MPa and the holding time is 10 s.

[0073] In step five, the green body is dried at a temperature of 100°C for 12 hours.

[0074] The firing process in step five involves uniformly raising the temperature from room temperature to 1320°C over 15 hours, holding it at that temperature for 30 minutes, and then allowing it to cool naturally back to room temperature.

[0075] The high-strength, high-whiteness, and high-transparency jade-like porcelain obtained in step five has a flexural strength of 110.38 MPa, a whiteness of 95.34%, and a light transmittance of 27.2%.

[0076] Example 7 A method for preparing a high-strength, high-whiteness, and high-transparency jade-like porcelain, characterized by comprising: a basic raw material A and other additive raw materials B. The weight percentage composition of the basic raw material A is as follows: potassium feldspar 40%, Guangxi kaolin 21%, quartz 28%, Malaysian kaolin 6%, bentonite 5%; The other additive material B is added according to the total weight of the base material A, namely 0.5% alumina, 2% lithium feldspar, 12.5% ​​Malaysian kaolin, and 3% nano-zirconia; The preparation method comprises the following steps: Step 1: Wet ball mill the base raw material A and other additive raw material B separately, and then pass them through an 80-mesh sieve to obtain the base raw material A slurry and the other additive raw material B slurry; Step 2: Pour the base material A slurry and the other additive material B slurry obtained in Step 1 into a plaster mold for dehydration and molding. Place the base material A blank and the other additive material B blank obtained after demolding in an oven to dry. Step 3: Crush the dried base material A blank and other additive material B blank into powder respectively, add water to adjust the powder moisture content to 6.5%, and then pass them through a 40-mesh sieve to obtain the base material A molding material and other additive material B molding material respectively; Step 4: First, pre-fire the other added raw material B molding material at 850℃ for 200 minutes, then crush it and pass it through a 120-mesh sieve. Then mix it with the basic raw material A molding material and dry ball mill it for 5 minutes to obtain a uniformly mixed jade porcelain mixed blank. Step 5: The jade-like porcelain mixed raw material obtained in Step 4 is granulated, shaped, dried, and fired in a reducing atmosphere to obtain high-strength, high-whiteness, and high-transparency jade-like porcelain.

[0077] In step one, the wet ball milling process has a material-to-ball-to-water mass ratio of 1:1.9:0.8, a ball milling speed of 350 r / min, and a ball milling time of 10 min.

[0078] The drying process in step two is carried out at a temperature of 80°C for 12 hours.

[0079] The particle size of the powder in the granulation process in step five is sieve size of 40 mesh.

[0080] In step five, the molding pressure is 20 MPa and the holding time is 8 seconds.

[0081] In step five, the green body is dried at a temperature of 100°C for 18 hours.

[0082] The firing process in step five involves uniformly raising the temperature from room temperature to 1300°C over 16 hours, holding it at that temperature for 30 minutes, and then allowing it to cool naturally back to room temperature.

[0083] The high-strength, high-whiteness, and high-transparency jade-like porcelain obtained in step five has a flexural strength of 121.93 MPa, a whiteness of 95.35%, and a light transmittance of 26.7%.

[0084] Comparative Example 1: To verify the superiority of Malaysian kaolin used in this invention, a comparative example was set up based on the raw material ratio, preparation process, and sintering regime of Example 2: only the Malaysian kaolin in Example 2 was replaced with an equal amount of New Zealand kaolin, while the other parameters remained unchanged, and the performance differences of the samples were compared.

[0085] The comparative sample made from New Zealand kaolin had a flexural strength of 105.02 MPa, a whiteness of 90.13%, and a light transmittance of 23.2%.

[0086] Depend on Figure 1As can be seen, after replacing the Malaysian kaolin in the formulation of Example 2 with New Zealand kaolin, the resulting comparative sample (C) had a smaller aperture, significantly reduced light transmittance, and poorer light transmittance uniformity.

[0087] Comparative Example 2:

[0088] To verify the effect of the pre-firing activation process of raw material B, a comparative example was set up based on the raw material ratio and sintering regime of Example 2: only the pre-firing process of raw material B in Example 2 was cancelled, and the other preparation operations remained unchanged.

[0089] The comparative sample formed using raw material B without pre-firing had a flexural strength of 104.47 MPa, a whiteness of 92.24%, and a light transmittance of 23.8%.

[0090] Depend on Figure 1 It is evident that after eliminating the pre-firing process of raw material B, the aperture of the resulting comparative sample (D) becomes smaller, the light transmittance decreases, and the uniformity of light transmission deteriorates.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the principles and spirit of the present invention are included within the protection scope of the present invention.

Claims

1. A method for preparing a high-strength, high-whiteness, and high-transparency jade-like porcelain, characterized in that: Includes basic raw material A and other additive raw material B. The weight percentage composition of the basic raw material A is as follows: potassium feldspar 40-52%, Guangxi kaolin 12-28%, quartz 18-28%, Malaysian kaolin 6-20%, and bentonite 1-5%; The other additive raw material B is added according to the total weight of the base raw material A, namely 0.5-10% alumina, 2-3% lepidolite, 5-13% Malaysian kaolin, and 0-4% nano-zirconia; The preparation method comprises the following steps: Step 1: Wet ball mill the base raw material A and other additive raw material B separately, and then pass them through an 80-120 mesh sieve to obtain the base raw material A slurry and the other additive raw material B slurry; Step 2: Pour the base material A slurry and the other additive material B slurry obtained in Step 1 into a plaster mold for dehydration and molding. Place the base material A blank and the other additive material B blank obtained after demolding in an oven to dry. Step 3: Crush the dried base material A blank and other additive material B blank into powder respectively, add water to adjust the moisture content of the powder to 5-7%, and then pass them through a 40-mesh sieve to obtain the base material A molding material and other additive material B molding material respectively. Step 4: Pre-fire the other added raw material B molding material at 750-850℃ for 200-300 minutes. After crushing, pass it through a 120-150 mesh sieve. Then mix it with the base raw material A molding material and dry ball mill for 3-5 minutes to obtain a uniformly mixed jade porcelain mixed blank. Step 5: The jade-like porcelain mixed raw material obtained in Step 4 is granulated, shaped, dried, and fired in a reducing atmosphere to obtain high-strength, high-whiteness, and high-transparency jade-like porcelain.

2. The preparation method according to claim 1, characterized in that: In step one, the wet ball milling process has a material-to-ball mill-to-water mass ratio of 1:1.8-2:0.5-1, a ball milling speed of 350 r / min, and a ball milling time of 10-25 min.

3. The preparation method according to claim 1, characterized in that: The drying process in step two is carried out at a temperature of 70–100°C for 10–16 hours.

4. The preparation method according to claim 1, characterized in that: The particle size of the powder in the granulation process in step five is sieve size of 40 mesh.

5. The preparation method according to claim 1, characterized in that: In step five, the molding pressure is 10–20 MPa and the holding time is 8–10 s.

6. The preparation method according to claim 1, characterized in that: In step five, the temperature for drying the green body is 70–100°C, and the time is 10–18 hours.

7. The preparation method according to claim 1, characterized in that: The firing process in step five involves uniformly raising the temperature from room temperature to 1260-1320°C over 10-16 hours, holding it at that temperature for 30-60 minutes, and then allowing it to cool naturally back to room temperature.

8. The preparation method according to claim 1, characterized in that: The high-strength, high-whiteness, and high-transparency jade-like porcelain obtained in step five has a flexural strength of 104.83–128.76 MPa, a whiteness of 94.63–95.35%, and a light transmittance of 26.5–28.8%.

Citation Information

Patent Citations

  • Preparation method of reinforced jade-based porcelain and product made of reinforced jade-based porcelain

    CN105060843A

  • Novel medium-temperature sintered feldspathic porcelain and preparation method thereof

    CN105218070A

  • High thermal-stability feldspar ceramic blank and preparation method of high thermal-stability feldspar ceramic product

    CN109081678A

  • Preparation method of high-strength ion exchange pre-stressed albite porcelain and porcelain product thereof

    CN109608181A

  • Low-density elongated stone porcelain ceramic plate and preparation method thereof

    CN113800880A